Estudis Històrics i Documents dels Arxius de Protocols, a journal on notaries and notarial documentation (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
This article presents in brief the trajectory of the review Estudis Històrics i Documents dels Arxius de Protocols, a publication established at the Notarial College of Barcelona in 1948. The article presents the context in which it was created, the three phases it has gone through and the main subjects it has dealt with.